Mobile phone rear cover with optical texture effect and preparation method thereof
By combining multi-layered structures and modified materials, the problems of diversification of magnetic ink texture effects and uneven printing were solved, realizing vivid and colorful graphic texture effects on the back cover of the mobile phone, and improving the mechanical strength and optical effect of the back cover of the mobile phone.
Patent Information
- Application Number
- CN202511089348.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2025-11-18
AI Technical Summary
In existing technologies, the background color of magnetic ink texture effects is too dark, making it difficult to achieve diverse designs. Furthermore, the high oil absorption of magnetic ink leads to uneven printing, affecting mobile phone performance.
It adopts a multi-layer structure consisting of a hardening liquid layer, an RGB graphic magnetic ink effect layer, a UV texture layer, an electroplating layer, an ink cap bottom layer, and an adhesive layer. Combined with modified resin and modified nano-neodymium iron boron hollow microspheres, it achieves graphic optical texture effects through the formulation of magnetic ink components and multi-layer functional design.
It achieves diverse and three-dimensional graphic texture effects, enhances the dispersibility and compatibility of magnetic ink, improves the mechanical strength and optical effect of mobile phone back covers, and meets consumer needs.
Smart Images

Figure CN120963188A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of mobile phone back cover manufacturing technology, specifically a mobile phone back cover with optical texture effect and its manufacturing method. Background Technology
[0002] With the development of mobile phone back cover design, the effects have become richer and more diverse, and these designs are highly favored by consumers. Magnetic ink texture effects have become an important process and method in the appearance of mobile phone back covers. The texture effect of magnetic ink moves with the angle of light, making it dynamic and ever-changing. Existing monochrome magnetic inks use iron oxide as the main component, presenting dark colors such as black or dark brown. This results in an overly dark background, making it difficult to cover complex patterns or achieve diverse designs. For example, a dark background significantly reduces the visibility of the color-changing effect, making it difficult to visually identify the anti-counterfeiting function of magnetic color-changing ink. Magnetic inks have a large oil absorption, resulting in poor ink flow, unstable transfer performance, and a tendency for ink piling or uneven printing. To improve printing performance, granular or cubic iron oxide materials are often added, but these materials have weak residual magnetism, and excessive use can affect mobile phone performance. This cannot meet the needs of more consumers. Therefore, this invention proposes a mobile phone back cover with optical texture effects and its preparation method to solve the above-mentioned technical problems. Summary of the Invention
[0003] The purpose of this invention is to provide a mobile phone back cover with optical texture effect and its manufacturing method, so as to solve the problems raised in the prior art.
[0004] To achieve the above objectives, the present invention provides the following technical solution: A mobile phone back cover with optical texture effect includes the following structure: from bottom to top, a hardening liquid layer, an RGB graphic magnetic ink effect layer, a UV texture layer, an electroplating layer, an ink cover bottom layer, an adhesive layer, and a 2D / 3D glass fiber electronic device back cover.
[0005] A method for manufacturing a mobile phone back cover with an optical texture effect includes the following processes: S1: Transfer release agent onto the base film to form a release film; S2: Coat the release film with a curing liquid to form a curing liquid layer; S3: Screen print R (red), G (green), and B (blue) three-color magnetic inks on the hardened liquid layer. When screen printing the three-color magnetic inks, screen print according to the corresponding RGB three-color screens, place them on the magnetic mold, and use the magnetic field of the mold to form an RGB three-color magnetic ink effect layer. S4: Transfer UV texture onto the RGB graphic magnetic ink effect layer to form a UV texture layer; S5: Indium tin oxide is deposited on the UV texture layer by PVD (physical vapor deposition) magnetron sputtering to form an electroplated layer; S6: Screen print ink onto the electroplated layer to cover the bottom layer, then bake and dry; S7: Apply or screen print adhesive on the bottom layer of the ink cap to form an adhesive layer; S8: Place the material coated or screen-printed with adhesive into the back cover of the 2D / 3D fiberglass electronic device and vacuum bond it; S9: After bonding, peel off the release film and base film to get a phone back cover with an optical texture effect.
[0006] In the above technical solution, magnetic inks offer a rich variety of colors, including red, green, blue, yellow, silver-white, black, and purple. Leveraging this rich color palette, computer graphics software (PS, AI) is used to separate the color channels of the graphic. RGB three-color gradient films are then created, along with corresponding RGB three-color gradient halftone screens. By printing the RGB three-color magnetic inks onto these screens, the optical texture effect of the graphic can be achieved. The graphic optical texture effect combines various magnetic ink color changes with magnetic textures to achieve complex graphic color and texture effects, resulting in diverse texture effects and vivid, three-dimensional graphics. The base film acts as a temporary carrier, and the release agent must possess controllable peeling force to ensure the subsequent coating can be completely transferred to the target surface, while the base film can be peeled off without residue. The curing liquid forms a transparent protective layer, enhancing surface hardness and scratch resistance. The base film uses a stretchable film as the substrate; it is peeled off after bonding with the release agent and does not adhere to the product surface. During screen printing of magnetic inks, the corresponding RGB three-color magnetic color effect layer is screen-printed according to the corresponding RGB three-color screen. The magnetic ink adheres to the surface of the cured layer, resulting in a clear and distinct pattern with chemical resistance. Magnetron sputtering is performed on the RGB three-color magnetic color effect layer to form an electroplated layer with transparent brightening, bright silver, or colored film effects. This multi-functional design overcomes the bottleneck in achieving complex patterns, meeting the needs of more consumers.
[0007] Furthermore, the base film is any one of ABS film, PO film, and PET film.
[0008] Furthermore, the thickness of the base film is 0.05~0.2mm.
[0009] Furthermore, the thickness of the release agent layer is 5~30μm.
[0010] Furthermore, the thickness of the hardening liquid layer is 10~30μm, and the hardening liquid permeability is >90%.
[0011] Furthermore, the thickness of the RGB graphic magnetic ink effect layer is 8~25μm.
[0012] Furthermore, the thickness of the UV texture layer is 5~20μm.
[0013] Furthermore, the thickness of the electroplated layer is 30~300nm.
[0014] Furthermore, the thickness of the ink undercoat layer is 40~60μm.
[0015] Furthermore, the thickness of the adhesive layer is 15~30μm.
[0016] Furthermore, the release agent is any one of silicone resin or polyurethane.
[0017] Furthermore, in step S2, the hardening fluid is LSP-8089.
[0018] Furthermore, in step S2, the coating process can be either roll coating or spray coating.
[0019] Furthermore, in step S3, the screen mesh size is 200-350 mesh.
[0020] Furthermore, the RGB three-color magnetic ink is prepared by the following process: Magnetic filler is added to the modified resin and dispersed at a speed of 3500~8000 r / min for 20~30 min under high shear dispersion. The pH is adjusted to 6.5~7.5 using 1 mol / L hydrochloric acid solution. Pigment and curing agent are added and stirred. Then defoamer and leveling agent are added to obtain magnetic ink. The magnetic ink is prepared in three parts, and the colors are selected in sequence as red, green and blue pigments to obtain RGB three-color magnetic ink.
[0021] Furthermore, the magnetic ink comprises the following components by weight: 10-20 parts pigment, 70-80 parts modified resin, 3-20 parts magnetic filler, 35-40 parts curing agent, 1-2 parts defoamer, and 1-2 parts leveling agent.
[0022] Furthermore, the curing agent is ethoxylated trimethylolpropane triacrylate.
[0023] Furthermore, the defoamer is an organosilicon defoamer, byk018.
[0024] Furthermore, the leveling agent is an organosilicon-based leveling agent, DC-57.
[0025] Furthermore, the modified resin is prepared by the following process: S3-1: Mix polyether glycol with hexamethylene diisocyanate, stir, add ethanol to obtain hydroxyl-terminated polyurethane prepolymer; S3-2: The hydroxyl-terminated polyurethane prepolymer is mixed with allyl glycidyl ether, and cashew phenol, crystal violet lactone (CVL) and dibutyltin dilaurate are added. The mixture is heated to react and the grafted prepolymer is obtained. S3-3: Add 2-hydroxyethyl acrylate to the grafted prepolymer, stir, and after the reaction is complete, distill under reduced pressure to obtain the modified resin.
[0026] In the above technical solution, the epoxy and hydroxyl groups of AGE (allyl glycidyl ether) undergo a ring-opening reaction, introducing allyl groups into the PUA (polyurethane acrylate) molecular chain, while retaining the acrylate double bonds to participate in UV curing crosslinking. The ether bonds generated after the ring-opening reaction improve the intermolecular forces, increasing the crosslinking and compatibility of the ink; the double bond structure balances the hardness and flexibility of PUA, reducing the risk of ink cracking; the polyether glycol reacts with hexamethylene diisocyanate and is capped in ethanol to generate a hydroxyl-terminated polyurethane prepolymer. The epoxy groups of AGE undergo nucleophilic ring-opening addition with the hydroxyl groups to generate modified segments linked by ether bonds. Under the action of a catalyst, the modified segments react with hydroxyethyl acrylate, and the remaining terminal isocyanate groups react with hydroxyethyl acrylate to generate urethane bonds, while the acrylate double bonds are retained at the ends of the molecular chain.
[0027] The introduction of allyl double bonds increases the density of double bonds in the molecular chain, and works synergistically with acrylate double bonds to accelerate UV curing. The introduction of the natural compound cashew phenol, through the condensation of the terminal hydroxyl polyurethane prepolymer with the phenolic hydroxyl groups, endows the ink with bioacceptability. At the same time, through hydroxyl crosslinking, a three-dimensional network structure is formed, which improves the mechanical strength of the resin system. By adding CVL, the color changes with temperature through an electron transfer mechanism. The opening and closing of the lactone ring of CVL are reversible. The ring opening forms a quinone structure with a conjugated structure, which absorbs visible light, and the ring closing restores the colorless state. This gives the resin system reversible color change and enriches the optical texture effect.
[0028] Furthermore, the mass ratio of polyether glycol, hexamethylene diisocyanate, and ethanol is (10~15):2:0.5.
[0029] Furthermore, the mass ratio of hydroxyl-terminated polyurethane prepolymer, allyl glycidyl ether, cashew phenol, CVL, and dibutyltin dilaurate is (50~60):(8~12):5:0.3:0.05.
[0030] Furthermore, the mass ratio of the grafted prepolymer to 2-hydroxyethyl acrylate is 10:(3~5).
[0031] Furthermore, the magnetic filler is modified neodymium iron boron nano-hollow microspheres.
[0032] Furthermore, the modified neodymium iron boron hollow microspheres are prepared by the following process: S4-1: Polystyrene (PS) microspheres are dispersed in polyacrylic acid, heated to react, and after the reaction is completed, centrifuged and dried to obtain pretreated PS microspheres; S4-2: Neodymium nitrate, ferric nitrate, and boric acid were mixed, ethanol solution was added, and the mixture was stirred. Citric acid solution was added, and pretreated PS microspheres were added. The mixture was ultrasonically dispersed, and the pH was adjusted under nitrogen protection. The mixture was stirred at a constant temperature. After the reaction was completed, the mixture was filtered and dried to obtain nano-neodymium iron boron microspheres. S4-3: Disperse neodymium iron boron nanospheres in tetrahydrofuran, heat to react, filter, centrifuge, and dry to obtain pretreated microspheres; S4-4: Disperse nano-neodymium iron boron hollow microspheres in an aqueous ethanol solution, add γ-methacryloyloxypropyltrimethoxysilane and dibutyltin dilaurate, heat to react, filter and dry after the reaction to obtain acryloxylated microspheres; S4-5: Hyaluronic acid was dissolved in deionized water, acryloyloxylated neodymium iron boron nanoparticles were added, ultrasonically dispersed, pH was adjusted, and the reaction was carried out. After the reaction was completed, the mixture was filtered and dried to obtain modified neodymium iron boron hollow microspheres.
[0033] In the above technical solution, a nano-neodymium iron boron hollow microsphere structure is prepared using the hard template method with PS as the hard template. Compared with conventional magnetic fillers (such as Fe3O4), it has the characteristics of being lightweight and having durable magnetic properties. During long-term storage, the pattern is not easily deformed. By modifying the surface of the nano-neodymium iron boron hollow microspheres, the microsphere surface and the coupling agent KH-570 (γ-methacryloyloxypropyltrimethoxysilane) undergo a condensation reaction under the action of the catalyst dibutyltin dilaurate. The group -CH2-CH2-CO-OC(CH3)=CH2 is grafted onto the surface of the microsphere as an active side link to obtain acryloyloxylated microspheres. The carboxylic acid group (-COOH) of hyaluronic acid (HA) undergoes an esterification reaction with acryloyloxy group, and hyaluronic acid is grafted onto the surface of acryloyloxylated microspheres to form a hydrophobic-hydrophilic balanced structure, which enhances the dispersibility and compatibility of the magnetic filler in the ink.
[0034] Furthermore, the mass ratio of polystyrene microspheres to polyacrylic acid is 1:(20~30).
[0035] Furthermore, the polystyrene microspheres have a particle size of 50-60 nm.
[0036] Furthermore, the mass ratio of neodymium nitrate, ferric nitrate, boric acid, and pretreated PS microspheres is (2~3):3:0.1:0.3.
[0037] Furthermore, the ethanol solution is a 70-75% vol% aqueous solution, accounting for 50-60% of the total mass of the reaction system.
[0038] Furthermore, the citric acid solution is a 1-2 mol / L aqueous solution, accounting for 1-5% of the total mass of the reaction system.
[0039] Furthermore, the mass ratio of neodymium iron boron nanospheres to tetrahydrofuran is 1:(10~50).
[0040] Furthermore, in steps S4-5, the process conditions for adjusting the pH are as follows: using a NaOH solution with a concentration of 3~5 mol / L to adjust the pH to 9~10.
[0041] Furthermore, the mass ratio of nano-neodymium iron boron hollow microspheres, ethanol aqueous solution, KH-570, and dibutyltin dilaurate is (3~5):80:2:0.02.
[0042] Furthermore, the mass ratio of hyaluronic acid, deionized water, and acryloyloxylated microspheres is (0.1~5):50:3.
[0043] Furthermore, the process conditions for the heating reaction are: reaction at 40~50℃ for 2~4 hours.
[0044] Furthermore, the drying process conditions are as follows: drying at a temperature of 60~70℃ for 1~2 hours.
[0045] Furthermore, the ultrasonic dispersion process conditions are as follows: disperse at a rotation speed of 1000~2000 r / min for 10~15 min.
[0046] Furthermore, the centrifugation process conditions are as follows: centrifuge at a speed of 2400~3000 r / min for 10~20 min.
[0047] Furthermore, in step S4, the specific process of transferring the UV texture layer is as follows: the UV curable resin system is uniformly coated on the RGB graphic magnetic ink effect layer, and the UV curable resin is pressed onto the UV lithography mold by a transfer machine using a UV lithography mold. The resin is then irradiated with a 250~400nm UV lamp for 1~2 minutes to cure. The UV curable resin is then released from the UV lithography mold to obtain the UV texture layer.
[0048] Furthermore, the UV-curable resin system includes the following components by weight: 40-60 parts of bisphenol A epoxy acrylate, 1-10 parts of photoinitiator 1173, and 40-50 parts of monomer TMPTA (trimethylolpropane triacrylate).
[0049] Furthermore, in step S5, the magnetron sputtering process conditions are as follows: ITO (indium tin oxide) is used as the target material, the target-substrate distance is 5~15cm, and an electroplating layer is deposited on the UV textured layer surface under the protective atmosphere of argon, with an electroplating power of 5~20W and a pressure of 0.1~5Pa.
[0050] In the above technical solution, indium tin oxide is selected as the target material, which has high light transmittance and electromagnetic shielding effect. A layer of indium tin oxide is magnetron sputtered on the optical texture layer, which can avoid the influence of magnetic ink on the performance of mobile phones.
[0051] Furthermore, in step S6, the baking and drying process conditions are: drying at a temperature of 80~120℃ for 20~40 minutes.
[0052] Furthermore, in step S7, the adhesive is any one of epoxy resin adhesive, acrylic adhesive, and polyurethane resin adhesive.
[0053] Furthermore, in step S8, the dimensions of the back cover are: (100~120)mm*(55~60)mm*(2~5)mm.
[0054] Furthermore, in step S8, the vacuum bonding process conditions are as follows: vacuum is maintained at a vacuum level of 0.08~0.1MPa for 5~15 minutes.
[0055] Compared with the prior art, the beneficial effects of the present invention are: 1. The mobile phone back cover of the present invention utilizes the graphic principle of R (red), G (green), and B (blue) three-color mode to screen print magnetic ink onto the 2D / 3D glass fiber / composite board mobile phone back cover, forming a three-dimensional, vivid, and colorful magnetic ink texture effect layer. The graphic texture effect is richer and more vivid, realizing more creative effects and meeting more consumer needs.
[0056] 2. The graphic texture effect of the mobile phone back cover of the present invention is not limited to the application of 2D / 3D glass fiber / composite board mobile phone back covers or other materials, but also includes the application of 2D electronic device back cover structure explosion-proof film and PET material.
[0057] 3. The mobile phone back cover of the present invention, through the formulation of magnetic ink components and the introduction of modified resin, endows the magnetic ink with bio-acceptability and improves the mechanical strength of the resin system; by adding CVL to the resin system, the opening and closing of the lactone ring of CVL are reversible, the opening ring forms a quinone structure with a conjugated structure, absorbs visible light, and the closing ring restores colorlessness; thus, the resin system has reversible color change, enriching the effect of optical texture.
[0058] 4. The mobile phone back cover of the present invention, by optimizing the composition and micro-design of the magnetic filler, endows the magnetic ink with the characteristics of lightweight and long-lasting magnetism, which is conducive to the long-term preservation of pattern texture effects, while enhancing the dispersibility and compatibility of the magnetic filler in the ink. Attached Figure Description
[0059] Figure 1 This is a process flow diagram of an embodiment of the present invention. Detailed Implementation
[0060] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0061] In the following specific embodiments, the number of "parts" referred to below refers to parts by mass; A mobile phone back cover with optical texture effect includes the following structure: from bottom to top, a hardening liquid layer, an RGB graphic magnetic ink effect layer, a UV texture layer, an electroplating layer, an ink cover bottom layer, an adhesive layer, and a 2D / 3D glass fiber electronic device back cover. Base film, PET base film, model T60, thickness 0.05mm; Release agent, silicone ester release agent, model SH-620; The pigments, namely Golden Red CP, Phthalocyanine Green 311, and Phthalocyanine Blue BGS, are sourced from Xinxiang Deke Effect Pigments Co., Ltd. Hardening fluid, model LSP-8089; The screen mesh size is 300. The UV-curable resin system comprises the following components by weight: 50 parts of bisphenol A epoxy acrylate, 10 parts of photoinitiator 1173, and 40 parts of monomer TMPTA (trimethylolpropane triacrylate). Bisphenol A epoxy acrylate (EBECRYL 600), molecular weight 484; Curing agent: ethoxylated trimethylolpropane triacrylate; The defoamer is an organosilicon defoamer, byk018; The leveling agent is an organosilicon-based leveling agent, DC-57. Polyether glycol, with a molecular weight of 600~1000; Polystyrene microspheres with a molecular weight of 10,000 to 50,000 and a particle size of 50 nm; Polyacrylic acid, with a molecular weight of 1000~5000; Adhesive, epoxy resin, model J-302; The dimensions of the phone's back cover are 100mm*55mm*3mm.
[0062] Example 1: A method for preparing a mobile phone back cover with an optical texture effect, comprising the following processes: S1: Transfer release agent onto the base film to form a release film; the thickness of the release agent layer is 5μm; S2: Coat the release film with a curing liquid to form a curing liquid layer; the thickness of the curing liquid layer is 10μm, and the permeability of the curing liquid is >90%; S3: Screen print R (red), G (green), and B (blue) three-color magnetic inks on the hardened liquid layer. When screen printing the three-color magnetic inks, screen print according to the corresponding RGB three-color screens, place them on a magnetic mold, and use the magnetic field of the mold to form an RGB three-color magnetic ink effect layer; the thickness of the RGB graphic magnetic ink effect layer is 8μm. S4: Transfer UV texture onto the RGB graphic magnetic ink effect layer. A UV-curable resin system is uniformly coated onto the RGB graphic magnetic ink effect layer. Using a UV photolithography mold, the UV-curable resin is pressed onto the UV photolithography mold using a transfer machine. The mold is then irradiated with a 350nm UV lamp for 1 minute to cure. The UV-curable resin is then released from the UV photolithography mold, resulting in a UV texture layer with a thickness of 5μm. S5: Indium tin oxide (ITO) was deposited on the UV texture layer by PVD (physical vapor deposition) magnetron sputtering. ITO was used as the target material with a target-substrate distance of 5 cm. Under the protective atmosphere of argon, an electroplating layer was deposited on the surface of the UV texture layer with an electroplating power of 5 W and a pressure of 0.1 Pa to form an electroplating layer with a thickness of 50 nm. S6: Screen print the ink base layer on the electroplated layer and dry it at 80°C for 20 minutes; the thickness of the ink base layer is 40μm. S7: Apply adhesive to the bottom layer of the ink cap to form an adhesive layer; the thickness of the adhesive layer is 15μm; S8: Place the material coated with adhesive into the back cover of the 2D / 3D glass fiber electronic device, and maintain the vacuum for 5 minutes at a vacuum level of 0.08MPa; S9: After lamination, peel off the release film and base film to obtain a phone back cover with an optical texture effect; The RGB (Red), G (Green), and B (Blue) three-color magnetic ink is prepared by the following process: Magnetic filler is added to modified resin, dispersed at 3500 r / min for 20 min under high shear dispersion, and the pH is adjusted to 6.5 using 1 mol / L hydrochloric acid solution. Pigment and curing agent are added, stirred, and then defoamer and leveling agent are added to obtain the magnetic ink. The magnetic ink comprises the following components by weight: 10 parts pigment, 70 parts modified resin, 3 parts magnetic filler, 35 parts curing agent, 1 part defoamer, and 1 part leveling agent. The magnetic ink consists of three parts, with the pigments selected sequentially as Golden Red CP, Phthalocyanine Green 311, and Phthalocyanine Blue BGS to obtain the RGB three-color magnetic ink. The modified resin is prepared by the following process: S3-1: Mix polyether glycol with hexamethylene diisocyanate, stir, and add ethanol to obtain a hydroxyl-terminated polyurethane prepolymer; the mass ratio of polyether glycol, hexamethylene diisocyanate, and ethanol is 10:2:0.5. S3-2: The hydroxyl-terminated polyurethane prepolymer was mixed with allyl glycidyl ether, and cashew phenol, crystal violet lactone (CVL), and dibutyltin dilaurate were added. The mixture was heated to react and obtain the grafted prepolymer. The mass ratio of the hydroxyl-terminated polyurethane prepolymer, allyl glycidyl ether, cashew phenol, CVL, and dibutyltin dilaurate was 50:8:5:0.3:0.05. S3-3: Add the grafted prepolymer to 2-hydroxyethyl acrylate, stir, and after the reaction is complete, distill under reduced pressure to obtain the modified resin; the mass ratio of grafted prepolymer to 2-hydroxyethyl acrylate is 10:3. Modified neodymium iron boron hollow microspheres were prepared by the following process: S4-1: Polystyrene (PS) microspheres were dispersed in polyacrylic acid and reacted at 40°C for 2 hours. After the reaction was completed, the mixture was centrifuged at 2400 r / min for 10 minutes and dried at 60°C for 1 hour to obtain pretreated PS microspheres. The mass ratio of polystyrene microspheres to polyacrylic acid was 1:20. S4-2: Neodymium nitrate, ferric nitrate, and boric acid were mixed, and 70 wt% ethanol aqueous solution was added. The mixture was stirred, and 1 mol / L citric acid aqueous solution was added. Pretreated PS microspheres were then added, and the mixture was dispersed at 1000 r / min for 10 min. Under nitrogen protection, the mixture was stirred at a constant temperature. After the reaction was completed, the mixture was filtered and dried to obtain nano-neodymium iron boron microspheres. The mass ratio of neodymium nitrate, ferric nitrate, boric acid, and pretreated PS microspheres was 2:3:0.1:0.3. S4-3: Disperse NdFeB nanospheres in tetrahydrofuran, react at 40℃ for 2h, filter, centrifuge at 2400r / min for 10min, and dry at 60℃ for 1h to obtain pretreated microspheres; the mass ratio of NdFeB nanospheres to tetrahydrofuran is 1:10. S4-4: NdFeB hollow nanospheres were dispersed in an ethanol aqueous solution, and γ-methacryloyloxypropyltrimethoxysilane and dibutyltin dilaurate were added. The reaction was carried out at 40°C for 2 hours. After the reaction was completed, the mixture was filtered and dried at 60°C for 1 hour to obtain acryloyloxylated microspheres. The mass ratio of NdFeB hollow nanospheres, ethanol aqueous solution, KH-570, and dibutyltin dilaurate was 3:80:2:0.02. S4-5: Hyaluronic acid was dissolved in deionized water, then acryloyloxylated neodymium iron boron nanoparticles were added and dispersed at 1000 r / min for 10 min. The pH was adjusted to 9 using a 3 mol / L NaOH solution. After the reaction was completed, the mixture was filtered and dried at 60℃ for 1 h to obtain modified neodymium iron boron hollow microspheres. The mass ratio of hyaluronic acid, deionized water, and acryloyloxylated microspheres was 0.1:50:3.
[0063] Example 2: This example provides a method for preparing a mobile phone back cover with an optical texture effect. In step S1, the thickness of the release agent is 20 μm; in step S2, the thickness of the curing liquid layer is 15 μm, and the transmittance of the curing liquid is >90%; in step S3, the thickness of the RGB graphic magnetic ink effect layer is 12 μm; in step S4, the thickness of the UV texture layer is 15 μm; in step S5, the thickness of the electroplating layer is 150 nm; in step S6, the thickness of the ink cover layer is 50 μm; in step S7, the thickness of the adhesive layer is 22 μm. In step S3, the magnetic ink comprises the following components by weight: 15 parts pigment, 75 parts modified resin, 10 parts magnetic filler, 37 parts curing agent, 1.5 parts defoamer, and 1.2 parts leveling agent. In step S5, the magnetron sputtering process conditions are as follows: ITO is used as the target material, the target-substrate distance is 10cm, and an electroplating layer is deposited on the UV textured layer surface under the protective atmosphere of argon, with an electroplating power of 8W and a pressure of 3Pa. The mass ratio of polyether glycol, hexamethylene diisocyanate, and ethanol is 12:2:0.5; The mass ratio of hydroxyl-terminated polyurethane prepolymer, allyl glycidyl ether, cashew phenol, CVL, and dibutyltin dilaurate is 55:10:5:0.3:0.05. The mass ratio of graft prepolymer to 2-hydroxyethyl acrylate is 10:4; The mass ratio of polystyrene microspheres to polyacrylic acid is 1:25; The mass ratio of neodymium nitrate, ferric nitrate, boric acid, and pretreated PS microspheres was 2.5:3:0.1:0.3. The mass ratio of neodymium iron boron nanospheres to tetrahydrofuran is 1:30; The mass ratio of nano-neodymium iron boron hollow microspheres, ethanol aqueous solution, KH-570, and dibutyltin dilaurate is 4:80:2:0.02; The mass ratio of hyaluronic acid, deionized water, and acryloyloxylated microspheres is 3:50:3; The other methods are the same as in Example 1.
[0064] Example 3: This example provides a method for preparing a mobile phone back cover with an optical texture effect. In step S1, the thickness of the release agent is 30 μm; in step S2, the thickness of the curing liquid layer is 30 μm, and the transmittance of the curing liquid is >90%; in step S3, the thickness of the RGB graphic magnetic ink effect layer is 25 μm; in step S4, the thickness of the UV texture layer is 20 μm; in step S5, the thickness of the electroplating layer is 300 nm; in step S6, the thickness of the ink cover layer is 60 μm; in step S7, the thickness of the adhesive layer is 30 μm. In step S3, the magnetic ink comprises the following components by weight: 20 parts pigment, 80 parts modified resin, 20 parts magnetic filler, 40 parts curing agent, 2 parts defoamer, and 2 parts leveling agent. In step S5, the magnetron sputtering process conditions are as follows: ITO is used as the target material, the target-substrate distance is 15cm, and an electroplating layer is deposited on the UV textured layer surface under the protective atmosphere of argon, with an electroplating power of 20W and a pressure of 5Pa. The mass ratio of polyether glycol, hexamethylene diisocyanate, and ethanol is 15:2:0.5; The mass ratio of hydroxyl-terminated polyurethane prepolymer, allyl glycidyl ether, cashew phenol, CVL, and dibutyltin dilaurate is 60:12:5:0.3:0.05. The mass ratio of graft prepolymer to 2-hydroxyethyl acrylate is 10:5; The mass ratio of polystyrene microspheres to polyacrylic acid is 1:30; The mass ratio of neodymium nitrate, ferric nitrate, boric acid, and pretreated PS microspheres was 3:3:0.1:0.3. The mass ratio of neodymium iron boron nanospheres to tetrahydrofuran is 1:50; The mass ratio of nano-neodymium iron boron hollow microspheres, ethanol aqueous solution, KH-570, and dibutyltin dilaurate is 5:80:2:0.02; The mass ratio of hyaluronic acid, deionized water, and acryloyloxylated microspheres is 5:50:3; The other methods are the same as in Example 1.
[0065] Comparative Example 1: This comparative example provides a method for preparing a mobile phone back cover with an optical texture effect. The pattern is drawn using conventional inks, and the rest of the method is the same as in Example 1.
[0066] Comparative Example 2: This comparative example provides a method for preparing a mobile phone back cover with an optical texture effect. Polyurethane acrylic resin is used instead of modified resin to prepare magnetic ink, and the rest of the method is the same as in Example 1.
[0067] Comparative Example 3: This comparative example provides a method for preparing a mobile phone back cover with an optical texture effect. It uses iron oxide instead of modified nano-neodymium iron boron hollow microspheres, and the rest of the method is the same as in Example 1.
[0068] Comparative Example 4: This comparative example provides a method for preparing a mobile phone back cover with an optical texture effect, using nano-neodymium iron boron hollow microspheres as magnetic fillers, and the rest of the method is the same as in Example 1.
[0069] Comparative Example 5: This comparative example provides a method for preparing a mobile phone back cover with an optical texture effect. In step S3-2, cashew phenol and crystal violet lactone are not added, and a resin system is prepared as a material for preparing magnetic fillers. The remaining methods are the same as in Example 1.
[0070] Experiment: Samples were prepared from the samples obtained in Examples 1-3 and Comparative Examples 1-5, and their performance was tested and the results were recorded. Color saturation test: Using ISO13660 as the reference standard, a colorimeter is used to test the color saturation of the sample and the test data is recorded.
[0071] Texture sharpness test: Using ISO25178-2:2021 as the reference standard, digital image processing method is adopted to extract the texture frequency domain features through Fourier transform and calculate the texture sharpness.
[0072] Transmittance test: Using GB / T2410-2008 as the reference standard, a detector is used to test the intensity of light after transmission and the intensity of light emitted from the light source. The transmittance is calculated by the ratio of the intensity of light received by the detector to the intensity of light emitted by the light source.
[0073] Tensile strength test: Using ISO6892-1 as the reference standard, a universal testing machine is used to apply a tensile force at a constant speed of 50 mm / min until the specimen breaks, and its tensile strength is recorded.
[0074] Environmental tolerance test: Using GB / T2423.3-2016 as the reference standard, the sample was placed in an environment of 85℃ and 80% humidity for 24 hours, and the color change and pattern adhesion effect were observed.
[0075] Cost-performance ratio comparison table index Color saturation (ΔE) Texture clarity (%) Light transmittance (%) Tensile strength (MPa) Environmental tolerance (good / average / poor) Example 1 1.2 95 92.5 235 better Example 2 1.0 94 93.1 241 better Example 3 0.9 98 91.8 239 better Comparative Example 1 5.8 70 85.2 198 generally Comparative Example 2 3.2 81 88.6 186 Poor Comparative Example 3 4.5 83 76.3 201 generally Comparative Example 4 2.8 71 89.5 181 Poor Comparative Example 5 1.3 82 92.0 228 generally Based on the data in the table above, the following conclusions can be clearly drawn: The results of comparing the back covers obtained in Examples 1-3 with those obtained in Comparative Examples 1-5 show that, compared with the comparative examples, the back covers with optical texture effects obtained in Examples 1-3 have lower color saturation, higher texture clarity, higher light transmittance, higher tensile strength, and better environmental resistance.
[0076] Compared with Example 1, the mobile phone back cover obtained in Comparative Example 1 has high saturation, low texture clarity, low light transmittance, low tensile strength, and average environmental resistance. This indicates that conventional inks lack the magnetic optimization and color channel separation technology of the present invention, resulting in a comprehensive decline in performance.
[0077] Compared with Example 1, the mobile phone back cover obtained in Comparative Example 2 has high saturation, low texture clarity, low light transmittance, low tensile strength, and poor environmental resistance. This indicates that no modified resin was used, resulting in poor resin crosslinking and lack of reversible color change, which affected durability and optical effects.
[0078] Compared with Example 1, the mobile phone back cover obtained in Comparative Example 3 has high saturation, low texture clarity, low light transmittance, low tensile strength, and general environmental resistance. The iron oxide filler lacks lightweight and durable magnetic properties and has not been surface modified, resulting in a decrease in light transmittance and compatibility.
[0079] Compared with Example 1, the mobile phone back cover obtained in Comparative Example 4 has high saturation, low texture clarity, low light transmittance, low tensile strength, and poor environmental resistance. This indicates that the surface modification of the nano-neodymium iron boron hollow microspheres was not performed, resulting in uneven dispersion of the filler in the ink and reducing the overall performance.
[0080] Compared with Example 1, the mobile phone back cover obtained in Comparative Example 5 has high saturation, low texture clarity, low light transmittance, low tensile strength, and general environmental tolerance. The surface lacks the reinforcing cross-linking effect of cashew phenol and the reversible color change of CVL, which limits the mechanical strength and optical effect of the resin system.
[0081] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A method for preparing a mobile phone back cover with an optical texture effect, characterized in that: The process includes the following steps: S1: Transferring a release agent onto the base film to form a release film; S2: Coat the release film with a curing liquid to form a curing liquid layer; S3: Screen print RGB three-color magnetic ink on the hardened liquid layer. When screen printing the three-color magnetic ink, screen print according to the corresponding RGB three-color screen, place it on the magnetic mold, and use the magnetic field of the mold to form the RGB three-color magnetic ink effect layer. S4: Transfer UV texture onto the RGB graphic magnetic ink effect layer to form a UV texture layer; S5: Indium tin oxide is deposited on the UV texture layer by PVD magnetron sputtering to form an electroplated layer; S6: Screen print ink onto the electroplated layer to cover the bottom layer, then bake and dry; S7: Apply or screen print adhesive PD onto the bottom layer of the ink cap to form an adhesive layer; S8: Place the material coated or screen-printed with adhesive into the back cover of the 2D / 3D fiberglass electronic device and vacuum bond it; S9: After bonding, peel off the release film and base film to get a phone back cover with an optical texture effect.
2. The method for preparing a mobile phone back cover with optical texture effect according to claim 1, characterized in that: The base film can be any one of ABS film, PO film, or PET film.
3. The method for preparing a mobile phone back cover with optical texture effect according to claim 2, characterized in that: The thickness of the base film is 0.05~0.2mm.
4. The method for preparing a mobile phone back cover with optical texture effect according to claim 1, characterized in that: The thickness of the release agent layer is 5~30μm.
5. The method for preparing a mobile phone back cover with optical texture effect according to claim 1, characterized in that: The thickness of the hardening liquid layer is 10~30μm, and the hardening liquid permeability is >90%.
6. The method for preparing a mobile phone back cover with optical texture effect according to claim 1, characterized in that: The RGB three-color magnetic ink is prepared by the following process: magnetic filler is added to modified resin, high shear dispersion is performed, pH is adjusted, pigment and curing agent are added, stirring is carried out, and then defoamer and leveling agent are added to obtain magnetic ink; the magnetic ink includes the following mass components: 10-20 parts pigment, 70-80 parts modified resin, 3-20 parts magnetic filler, 35-40 parts curing agent, 1-2 parts defoamer, and 1-2 parts leveling agent; the magnetic ink consists of three parts, and the pigments are selected in sequence as red, green, and blue pigments to obtain RGB three-color magnetic ink.
7. A method for preparing a mobile phone back cover with optical texture effect according to claim 6, characterized in that: The modified resin is obtained by the following process: S3-1: Mix polyether glycol with hexamethylene diisocyanate, stir, and add ethanol to obtain hydroxyl-terminated polyurethane prepolymer; the mass ratio of polyether glycol, hexamethylene diisocyanate and ethanol is (10~15):2:0.5; S3-2: The hydroxyl-terminated polyurethane prepolymer is mixed with allyl glycidyl ether, and cashew phenol, crystal violet lactone, and dibutyltin dilaurate are added. The mixture is heated to react and obtain the grafted prepolymer. The mass ratio of the hydroxyl-terminated polyurethane prepolymer, allyl glycidyl ether, cashew phenol, CVL, and dibutyltin dilaurate is (50~60):(8~12):5:0.3:0.
05. S3-3: Add the grafted prepolymer to 2-hydroxyethyl acrylate, stir, and after the reaction is complete, distill under reduced pressure to obtain the modified resin; the mass ratio of grafted prepolymer to 2-hydroxyethyl acrylate is 10:(3~5).
8. The method for preparing a mobile phone back cover with optical texture effect according to claim 6, characterized in that: The magnetic filler is modified neodymium iron boron hollow microspheres; the modified neodymium iron boron hollow microspheres are prepared by the following process: S4-1: Polystyrene microspheres are dispersed in polyacrylic acid, heated to react, and after the reaction is completed, centrifuged and dried to obtain pretreated PS microspheres; the microspheres have a particle size of 50~60nm. S4-2: Neodymium nitrate, ferric nitrate, and boric acid were mixed, and an ethanol solution was added. The mixture was stirred, and a citric acid solution was added. Pretreated PS microspheres were then added and ultrasonically dispersed. The mixture was stirred at a constant temperature under nitrogen protection. After the reaction was completed, the mixture was filtered and dried to obtain nano-neodymium iron boron microspheres. The mass ratio of neodymium nitrate, ferric nitrate, boric acid, and pretreated PS microspheres was (2~3):3:0.1:0.
3. S4-3: Disperse neodymium iron boron nanospheres in tetrahydrofuran, heat to react, filter, centrifuge, and dry to obtain pretreated microspheres; S4-4: Disperse nano-neodymium iron boron hollow microspheres in an aqueous ethanol solution, add γ-methacryloyloxypropyltrimethoxysilane and dibutyltin dilaurate, heat to react, filter and dry after the reaction to obtain acryloxylated microspheres; S4-5: Hyaluronic acid was dissolved in deionized water, acryloyloxylated neodymium iron boron nanoparticles were added, ultrasonically dispersed, pH was adjusted, and the reaction was carried out. After the reaction was completed, the mixture was filtered and dried to obtain modified neodymium iron boron hollow microspheres. The mass ratio of hyaluronic acid, deionized water, and acryloyloxylated microspheres was (0.1~5):50:
3.
9. A method for preparing a mobile phone back cover with optical texture effect according to claim 1, characterized in that: In step S4, the specific process of transferring the UV texture layer is as follows: the UV-curable resin system is uniformly coated on the RGB graphic magnetic ink effect layer, and the UV-curable resin is pressed onto the UV-lithography mold by a transfer machine using a UV photolithography mold. It is then irradiated with a 250~400nm UV lamp for 1~2 minutes to cure. The UV-curable resin is then released from the UV photolithography mold to obtain the UV texture layer. The UV-curable resin system includes the following components by mass: 40~60 parts of bisphenol A epoxy acrylate, 1~10 parts of photoinitiator 1173, and 40~50 parts of monomer TMPTA.
10. A mobile phone back cover with an optical texture effect, characterized in that: Prepared by the preparation method according to any one of claims 1-9.